Effect of Change in Land-use to High Pattern of Inundation on Sub-River System of Lowland Urban River - Hamim S.A.; Usman F. (IOP Publishing Ltd, 2023)
Flooding is a temporal condition of surface water where the level and debit are exceeding a specific allowable limit. Urban city flooding is an effect of unbalance city environment related to regulation function. Vulnerability to increasing of population and change of land use at rural area and urbanisation to the flood-prone area, illegal shelter, land development on the water catchment area, increase in population density are the most common source of flooding on an urban area. This paper presents a study on the effect of changing in land use to high inundation pattern on river sub-system (SRS) of Bendung River in Palembang City. The data is taken based on a digital elevation model (DEM) generated from high point data set from a Compact Airborne Spectrographic Imager (CASI) sensor. The model used in this study was a hydrological model using SMADA 6.0 and DUFLOW 3.6 for rainfall-runoff model and analysis of river system generating surface water profile. The ArcGIS was used to construct a surface water model related to DEM data to obtain inundated area, inundation maps, inundation height and geospatial analysis. Four scenarios are applied in this study area which was changing the type of land use to a green area, changing the type of land use to a settlement area, free up 30 m riverbank to a green area and free up 100 m riverbank to a green area. From this study, the change in runoff coefficient, C value does not significantly reduce the inundation area in the area with more than 80% relatively flat topography. Increase the C value by 10% resulted in an increase on the puddle area to 9.4%, while the flood area with an altitude of more than 1 m increased to 359%. The results of scenario with land used change 10% - 20%, contributed to the increase in the flood area of 9.4% - 12.1%. So that to reduce the high pattern inundation a structural approach combined with a non-structural approach should be enforced and implemented. Besides, land-use changes will be significant to reduce flooding when land consolidation is applied to a sub-river system (SRS). Published under licence by IOP Publishing Ltd.